How Well the Government of Nepal Is Responding to COVID-19? An Experience From a Resource-Limited Country to Confront Unprecedented Pandemic - Rayamajhee, Binod; Pokhrel, Anil; Syangtan, Gopiram; Khadka, Saroj; Lama, Bhupendra; Rawal, Lal Bahadur; Mehata, Suresh; Mishra, Shyam Kumar; Pokhrel, Roshan; Yadav, Uday Narayan (Frontiers in Public Health, 2021)
COVID-19, caused by SARS-CoV-2, was first reported in Wuhan, China and is now a pandemic affecting over 218 countries and territories around the world. Nepal has been severely affected by it, with an increasing number of confirmed cases and casualties in recent days, even after 8 months of the first case detected in China. As of 26 November 2020, there were over 227,600 confirmed cases of COVID in Nepal with 209,435 recovered cases and 1,412 deaths. This study aimed to compile public data available from the Ministry of Health and Population (MoHP), Government of Nepal (GoN) and analyse the data of 104 deceased COVID-19 patients using IBM SPSS (Version 25.0). Additionally, this study also aimed to provide critical insights on response of the GoN to COVID-19 and way forward to confront unprecedented pandemic. Figures and maps were created using the Origin Lab (Version 2018) and QGIS (Version 3.10.8). Most of the reported cases were from Bagmati Province, the location of Nepal's capital city, Kathmandu. Among deceased cases, >69% of the patients were male and patients ≥54 years accounted for 67.9% (n = 923). Preliminary findings showed respiratory illness, diabetes, and chronic kidney diseases were the most common comorbid conditions associated with COVID-19 deaths in Nepal. Despite some efforts in the 8 months since the first case was detected, the government's response so far has been insufficient. Since the government eased the lockdown in July 2020, Nepal is facing a flood of COVID-19 cases. If no aggressive actions are taken, the epidemic is likely to result in significant morbidity and mortality in Nepal. The best way to curb the effect of the ongoing pandemic in a resource-limited country like Nepal is to increase testing, tracing, and isolation capacity, and to set up quality quarantine centers throughout the nation. A comprehensive health literacy campaign, quality care of older adults and those with comorbidity will also result in the effective management of the ongoing pandemic.